Pengaruh Media Sosial Pada Perilaku Belajar PAI Pada Kurikulum Merdeka - Melina, Novita Peggy; Safitri, Yuni; Abdullah, Mu'in (An-Nuha, 2025)
This study investigates the impact of social media on the learning behaviors associated with Islamic religious education within the framework of the Merdeka curriculum at Muhammadiyah 1 Sukoharjo High School. Employing a quantitative methodology, the research involved students from the 10th and 11th grades, selected through Probability Sampling techniques. Data were gathered via questionnaires and subsequently analyzed using descriptive statistics alongside SPSS version 25. 0. The findings indicated that the use of social media fell within the "medium" category, with 14 students classified under this designation, while learning behavior also aligned with the "medium" category, encompassing 9 students. The Kolmogorov-Smirnov normality test produced a significance value of 0. 200, exceeding the 0. 05 threshold, while the linearity test yielded a significance value of 0. 764, also greater than 0. 05. Furthermore, the product moment hypothesis test resulted in a significance value of 0. 008.